Activation of human platelets by 2-arachidonoylglycerol is enhanced by serotonin - Maccarrone, Mauro; Bari, Monica; Del Principe, Domenico; Finazzi-Agrò, Alessandro (Thrombosis and Haemostasis, 2003)
The endocannabinoid 2-arachidonoylglycerol (2-AG) has been shown to activate human platelets in platelet-rich plasma, by binding to a “platelet-type” cannabinoid receptor (CBPT). Here, washed human platelets were used to characterize the binding of [3H]2-AG to CBPT, showing a dissociation constant (Kd) of 140 ± 31 nM and a maximum binding (Bmax) of 122 ± 10 pmol.mg protein-1. Selective antagonists of both CB1 and CB2 cannabinoid receptors inhibited this binding, which was enhanced up to ~230% over the controls by 1 µM serotonin (5-hydroxytryptamine, 5-HT). Human platelets were also able to bind [3H]5-HT (Kd = 79 ± 17 nM, Bmax = 14.6 ± 1.3 pmol.mg protein-1), and 1 µM 2-AG enhanced this binding up to ~150%. Moreover, they were able to take up [3H]5-HT through a high affinity transporter (Michaelis-Menten constant = 22 ± 2 nM, maximum velocity = 344 ± 15 pmol.min-1.mg protein-1), which was not affected by 2-AG. Interestingly, 5-HT did not affect the activity of the 2-AG transporter of human platelets. Treatment of washed platelets with 1 µM 2-AG led to increased intracellular inositol-1,4,5-trisphosphate (up to ~300%) and decreased cyclic AMP (down to ~50%). Furthermore, treatment of pre-loaded platelets with 1 µM 2-AG induced a ~300% increase in [3H]2-AG release, according to a CBPT-dependent mechanism. Also, 1 µM 5-HT enhanced the effect of 2-AG on inositol-1,4,5-trisphosphate (~500% of the controls), cyclic AMP (~20%) and [3H]2-AG release (~570%), and the latter process was shown to be partly (~50%) involved in the 5-HT-dependent platelet activation. Taken together, reported findings represent the first demonstration that 2-AG and 5-HT can mutually reinforce their receptor binding on platelet surface, which might have therapeutic implications.
Keywords: Agonists; cyclic AMP; endocannabinoids; inositol-1,4,5-trisphosphate; receptors; transporters